Terapia de movimiento inducido por restricción del lado sano en adultos post accidente cerebrovascular. - Naranjo Ruiz, Paola Stefanía (2024)
Stroke can be caused by a reduction or restriction of blood flow to the brain, resulting in hemiplegia or hemiparesis, which can impair everyday responsibilities. As a result, constraint-induced movement therapy on the unaffected side serves as neurorehabilitation, improving the functional limitations of the affected upper limb. The present study aims to determine the effect of healthy side constraint-induced movement therapy as a neurorehabilitation technique in the hemiplegic upper limb in post-stroke patients. A documentary design methodology and bibliographic type was used, by reviewing information in the following databases: Scielo, PubMed, PEDro, Scopus, ScienceDirect; using keywords and descriptors, as well as Boolean operators. Finally, 72 articles were identified and through the identification, filtering, pre-analysis, inclusion and application of the Physiotherapy Evidence Database scale, 26 randomized clinical trials were identified, whose information met the inclusion and exclusion criteria, being the basis for the documentary development of the present study. The studies show that restriction-induced movement therapy on the healthy side has positive effects on the affected upper limb in adult post-stroke patients, achieving a better quality of life by achieving autonomy for daily activities.